The role of developmental plasticity in evolutionary innovation - Moczek, Armin P. (The Royal Society, 2011)
Explaining the origins of novel traits is central to evolutionary biology. Longstanding theory suggests that developmental plasticity, the ability of an individual to modify its development in response to environmental conditions, might facilitate the evolution of novel traits. Yet whether and how such developmental flexibility promotes innovations that persist over evolutionary time remains unclear. Here, we examine three distinct ways by which developmental plasticity can promote evolutionary innovation. First, we show how the process of genetic accommodation provides a feasible and possibly common avenue by which environmentally induced phenotypes can become subject to heritable modification. Second, we posit that the developmental underpinnings of plasticity increase the degrees of freedom by which environmental and genetic factors influence ontogeny, thereby diversifying targets for evolutionary processes to act on and increasing opportunities for the construction of novel, functional and potentially adaptive phenotypes. Finally, we examine the developmental genetic architectures of environment-dependent trait expression, and highlight their specific implications for the evolutionary origin of novel traits. We critically review the empirical evidence supporting each of these processes, and propose future experiments and tests that would further illuminate the interplay between environmental factors, condition-dependent development, and the initiation and elaboration of novel phenotypes.